تجارب الوقف المؤقت وإمكانية تفعيلها في ماليزيا : دراسة تأصيلية فقهية - Muhammad Firdaus bin Ab Rahman (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
Muslim jurists differ in the declaration (sighah) of waqf, specifically on whether a waqf can be made temporary or it is limited to perpetuity. In Malaysia, most of the states impose waqf solely on perpetuity based on the Shafi،i School of Islamic law. The objectives of this thesis are to critically examine the definition of waqf and its pillars, to assess the different opinions of the scholars on the issue of temporary waqf, to explore the implementation of temporary waqf in selected Muslim countries, to analyse the interview sessions with selected states in Malaysia on temporary waqf, to establish the principles of temporary waqf implementation and to suggest new approaches of temporary waqf which may be implemented in Malaysia. A qualitative methodology was employed to analyse the data through inductive, deductive and field research methods. The inductive, deductive and comparative methods were used to research the main sources of literature and to analyse the issues related to temporary waqf. As for the field research, this thesis has conducted semi-structured interviews with the Waqf Corporations and Mufti's Department in the selected states of Malaysia, namely, Selangor, Melaka, Negeri Sembilan and Johor. The findings show that waqf is not limited only to perpetuity. Hence, some jurists such as Maliki School of Islamic law approves the application of temporary and perpetual waqf. Temporary waqf is divided into three sections; temporary in the siqhah, temporary in the beneficiaries of the waqf (mawquf ،alayh) and temporary in the waqf properties (mawquf). Furthermore, when the donor (waqif) has identified a specific duration of the waqf, it will be considered as one of the valid conditions. Thus, there is a need for temporary waqf to be enacted and applied in Malaysia as it provides the best interests (maslahah) for donors, beneficiaries and the community at large. Impliedly, Islamic legal pronouncements (fatwa's) which were issued by the State Fatwa Committee in Malaysia, have to be reassessed from time to time and should not be limited to the view of a single school of Islamic law, especially in the field of waqf, without considering the maslahah of donors, waqf properties and contemporary society.